2023
DOI: 10.1038/s41467-023-35860-2
|View full text |Cite|
|
Sign up to set email alerts
|

Near-infrared-featured broadband CO2 reduction with water to hydrocarbons by surface plasmon

Abstract: Imitating the natural photosynthesis to synthesize hydrocarbon fuels represents a viable strategy for solar-to-chemical energy conversion, where utilizing low-energy photons, especially near-infrared photons, has been the ultimate yet challenging aim to further improving conversion efficiency. Plasmonic metals have proven their ability in absorbing low-energy photons, however, it remains an obstacle in effectively coupling this energy into reactant molecules. Here we report the broadband plasmon-induced CO2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 42 publications
0
59
0
Order By: Relevance
“…Moreover, the formed CO bound strongly to the Cu sites to experience further hydrogenation for CH 4 production. Most recently, Hu et al reported the Au rod@CuPd 2 core–shell composite for broadband CO 2 reduction with H 2 O (Figure g) . It was reported that the Au plasmon-induced local electric field facilitated i) the formation of quasi isolated trap states above the Fermi level of the hybrid state between CO 2 and CuPd (extending the lifetime of hot carriers) and ii) the selective energy transfer to CO 2 than H 2 O (limiting the competitive H 2 production reaction).…”
Section: Active Site-engineered Plasmonic Nanostructures For Emerging...mentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the formed CO bound strongly to the Cu sites to experience further hydrogenation for CH 4 production. Most recently, Hu et al reported the Au rod@CuPd 2 core–shell composite for broadband CO 2 reduction with H 2 O (Figure g) . It was reported that the Au plasmon-induced local electric field facilitated i) the formation of quasi isolated trap states above the Fermi level of the hybrid state between CO 2 and CuPd (extending the lifetime of hot carriers) and ii) the selective energy transfer to CO 2 than H 2 O (limiting the competitive H 2 production reaction).…”
Section: Active Site-engineered Plasmonic Nanostructures For Emerging...mentioning
confidence: 99%
“…Most recently, Hu et al reported the Au rod@CuPd 2 core−shell composite for broadband CO 2 reduction with H 2 O (Figure 13g). 11 It was reported that the Au plasmon-induced local electric field facilitated i) the formation of quasi isolated trap states above the Fermi level of the hybrid state between CO 2 and CuPd (extending the lifetime of hot carriers) and ii) the selective energy transfer to CO 2 than H 2 O (limiting the competitive H 2 production reaction). In addition, a spherical reactor design for gas−solid phase CO 2 reduction was proposed to enable the reincidence of scattered photons, leading to high photon utilization efficiency.…”
Section: Active Site-engineered Plasmonic Nanostructures For Emerging...mentioning
confidence: 99%
See 3 more Smart Citations